2018
DOI: 10.1101/418590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative multi-locus metabarcoding and waggle dance interpretation reveal honey bee spring foraging patterns in Midwest agroecosystems

Abstract: We explored the pollen foraging behavior of honey bee colonies situated in the corn and soybean dominated agroecosystems of central Ohio over a month-long period using both pollen metabarcoding and waggle dance inference of spatial foraging patterns. For molecular pollen analysis we developed simple and cost-effective laboratory and bioinformatics methods. Targeting four plant barcode loci (ITS2, rbcL, trnL and trnH), we implemented metabarcoding library preparation and dual-indexing protocols designed to mini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…In this study, we investigated whether it is possible to predict the abundance of DNA sequencing reads from the quantities of pollen grains and if so, how accurately, and how the prediction is affected by the methodology used to estimate pollen abundances in mock solutions, PCR conditions, plant species and the type of markers (nuclear versus plastid). In agreement with previous studies [20][21][22]25,40 but in contrast to others 17,26,30,31 , we found a significant, and often strong positive relationship between the number of DNA sequences and the number of pollen grains in the mock solutions. However, the strength of the relationship was influenced by the pollen counting methodology, the marker, the species and the number of PCR cycles.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, we investigated whether it is possible to predict the abundance of DNA sequencing reads from the quantities of pollen grains and if so, how accurately, and how the prediction is affected by the methodology used to estimate pollen abundances in mock solutions, PCR conditions, plant species and the type of markers (nuclear versus plastid). In agreement with previous studies [20][21][22]25,40 but in contrast to others 17,26,30,31 , we found a significant, and often strong positive relationship between the number of DNA sequences and the number of pollen grains in the mock solutions. However, the strength of the relationship was influenced by the pollen counting methodology, the marker, the species and the number of PCR cycles.…”
Section: Discussionsupporting
confidence: 91%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Effects of molecular markers and PCR conditions. We found that for trnL, very accurate prediction of DNA read abundance was obtained from pollen grain quantities estimated by light microscopy, with determination coefficients and slopes generally higher than those found in the literature with the same markers 40 or with other markers 17,21,26,30,31 . Moreover, except at PCR25, the good relationship was conserved across species and PCR cycles and trnL sequence abundance increased steadily with increasing PCR cycles.…”
Section: Efficiency Of Microscopy Vs Flow Cytometry In Counting Pollementioning
confidence: 50%
See 3 more Smart Citations